Implementasi Model Pembelajaran Jig Saw terhadap Hasil Belajar Siswa di kelas X-11 SMA Negeri 5 Semarang dalam Mata Pelajaran Pendidikan Pancasila Materi Hak dan Kewajiban sebagai Warga Sekolah, Masyarakat, dan Negara - Iman Setiawan, Dhandi; Sudrajat, Rahmat; Sri Wahyuni, Endang (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2024)
The aim of this classroom action research is to: Improve student learning outcomes in Bhinneka Tunggal Ika material through the Jig Saw learning model. To achieve this goal, this research was carried out through two cycles. The procedure for each cycle includes the following stages: 1) Action plan, 2) Implementation of action, 3) Observation stage, 4) Reflection. The results of classroom action research in the initial condition of low student motivation and learning outcomes, the teacher applied the Jig Saw learning model. This low motivation can be seen from the actions of students who easily get bored when learning, looking sleepy, propping their chins, the class conditions are noisy, and students are easily distracted by other things. However, after receiving action, students’ motivation increased from being in the medium category to the high category. Students’ attitudes also show changes to become more active. It can be seen by changes in the attitudes of students who are present in learning, active when taking part in group work, active when carrying out questions and answers in class. Student learning outcomes before taking action reached 69.8 or only had a student completion percentage of only 27.7%. This figure does not meet the specified criteria, namely the minimum completion limit of 75 or above or 85%. Therefore, action is needed to improve student learning outcomes using the Jig Saw model. Meanwhile, student learning outcomes after taking action in cycle I reached 77.77% and cycle II increased to 91.66%.